A THEORETICAL FRAMEWORK OF COMPETITVE ADVANTAGE FOR SMES IN CHINA UNDER NEW NORMAL ECONOMY - Yan, Shigang (European Scientific Journal, ESJ, 2015)
Small and medium-sized enterprises (SMEs) have grown to be an important force in promoting the development of the Chinese economy. As China’s economy is making a shift towards new normal stage, Chinese SMEs are facing a myriad of problems and difficulties which have constrained their further development. The research integrates the industry organization approach and resource-based view which have emerged in the literature related to the concept of competitive advantage. Based on these two approaches, a theoretical framework is developed to put forward that Chinese SMEs’ competitive advantage depends upon the identification of appropriate strategy and industry structure as well as developing and creating core capability in order to exploit opportunities and neutralize the threats faced in new normal economy.